THE TOOLING IN UKRAINE OF MODEL TESTS OF OBJECTS OF ENERGY, AVIATION AND SPACE-ROCKET ENGINEERING ON RESISTIBILITY TO ACTION OF PULSED CURRENT OF ARTIFICIAL LIGHTNING - M. I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2018)
Purpose. Presentation and analysis of the modern state of the tooling in Ukraine of model tests of objects of energy, aviation and space-rocket engineering on resistibility to the action of pulsed current of artificial lightning. Methodology. Electrophysics bases of technique of high-voltage and high pulsed currents, theoretical bases of electrical engineering, engineering of high electric and magnetic fields. Scientific methods of analysis of research and technical information. Results. Information regarding the modern consisting of Ukraine of high-voltage high-current pulsed engineering intended for the leadthrough of model tests of aircrafts and power objects on resistibility to the direct or indirect action on them of pulsed current of artificial lightning in accordance with the requirements of normative documents of the USA SAE ARP 5412: 2013, SAE ARP 5416: 2013 and International Standard IEC 62305-1: 2010. Basic technical descriptions are presented of developed and created in Ukraine for the aims of model tests of the technical objects marked higher on resistibility to lightning of two powerful high-voltage generators of current of lightning (GCL) of type of UITOM-1 and GTM-10/350, playback on the tested objects the pulses of current of artificial lightning with the rationed peak-temporal parameters in obedience to the indicated normatively-technical documents. Examples are resulted and the results of model tests are indicated on described domestic GCL of some elements and devices of the tested technical objects on resistibility to direct action on them of pulsed current of artificial lightning. It is shown that technical descriptions indicated domestic powerful GCL conform to the high requirements of operating in the leading countries of the world of normative documents to on resistibility to lightning objects of industrial energy, aviation and space-rocket engineering. Originality. First in the summarizing concentrated kind possibilities are shown developed and created domestic scientists and specialists of unique high-voltage high-current electrophysics equipment for the aims of leadthrough of integration model tests on resistibility and fire safety of aircrafts and power objects at lightning strike. Practical value. Application in practice of model tests of objects of industrial energy, aviation and space-rocket engineering on complex resistibility and fire safety to the striking action on them of pulsed current of artificial lightning, generated in discharge circuits of two described powerful domestic GCL, will be instrumental in the successful decision of global in the world problem of protecting from lightning of air and surface technical objects and being in them personnel.